2011
DOI: 10.1590/s1676-06032011000100040
|View full text |Cite
|
Sign up to set email alerts
|

Nota sobre abelhas Lestrimelitta rufipes (Freise) (Hymenoptera, Meliponina), atraídas por armadilhas com iscas odoríferas, na região Sul Fluminense do Estado do Rio de Janeiro

Abstract: This study was done each two months between August 2006 to May 2007 in a South Region in the State of Rio de Janeiro. The traps, a (Carvalho-47) model, were adjusted, then assembled at 9 o'clock and finally removed 48 hours after. In each place of the extraction, 4 traps were assembled, in a total of 20 in all the trail. During the experiment, eight worker bees of Lestrimelitta rufipes, were captured, and seven of them were attracted by methyl salicilate and one by cineole. Beside this essences, two more were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…Nevertheless, even with some sampling design limitations, our results showed that scent traps successfully collected specific groups of bees. Although this kind of trapping method was developed and is mainly used to sample orchid bees (Euglossini) (Dressler, 1982), our results corroborate some literature records of other non-target bee groups being attracted to the scents (Alves et al, 2011;Nemésio & Siqueira, 2011;Knoll & Santos, 2012). This observation points to the possibility of extending the usage of this kind of trap to studies focused on additional target groups, including hard-to-sample nocturnal bees such as Megalopta (Carvalho et al, 2012).…”
Section: Discussionsupporting
confidence: 87%
“…Nevertheless, even with some sampling design limitations, our results showed that scent traps successfully collected specific groups of bees. Although this kind of trapping method was developed and is mainly used to sample orchid bees (Euglossini) (Dressler, 1982), our results corroborate some literature records of other non-target bee groups being attracted to the scents (Alves et al, 2011;Nemésio & Siqueira, 2011;Knoll & Santos, 2012). This observation points to the possibility of extending the usage of this kind of trap to studies focused on additional target groups, including hard-to-sample nocturnal bees such as Megalopta (Carvalho et al, 2012).…”
Section: Discussionsupporting
confidence: 87%